2002
DOI: 10.1039/b201901a
|View full text |Cite
|
Sign up to set email alerts
|

New stereoselective reaction of methylglyoxal with 2-aminopyridine and adenine derivatives: Formation of imino acid-nucleic base derivatives in water under mild conditions

Abstract: A remarkable stereoselective reaction of methylglyoxal with 2-aminopyridine, the nucleic base adenine and adenine nucleosides leads in good yield to heterocycles of a new family in water under mild conditions and should be of interest in the understanding of the biological effects of methylglyoxal which is toxic, mutagenic and involved in diabetic complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…The enantiomers 2a and their isomers 2b obtained from 2-aminopyridine and the corresponding adenine adducts 4a have been characterized by X-ray crystallography ( Fig. 2) (Routaboul et al, 2002). After the reaction and removal of methylglyoxal in excess, the isomers a and b could be detected by NMR spectrometry in a ratio of 60:40.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The enantiomers 2a and their isomers 2b obtained from 2-aminopyridine and the corresponding adenine adducts 4a have been characterized by X-ray crystallography ( Fig. 2) (Routaboul et al, 2002). After the reaction and removal of methylglyoxal in excess, the isomers a and b could be detected by NMR spectrometry in a ratio of 60:40.…”
Section: Resultsmentioning
confidence: 99%
“…2). Both diastereomers a and b could be detected by NMR spectrometry but could not be separated (Routaboul et al, 2002). To modulate the lipophily of the adducts, new methylglyoxal adducts 3a,b, 7a,b, and 8a,b were prepared.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1a) is a very potent CFTR inhibitor [13,14]. Here, following a structure-activity study, we identified methylglyoxal-9-propyladenine adducts ( fig.…”
mentioning
confidence: 99%